Urolithin A alleviates cell senescence by inhibiting ferroptosis and enhances corneal epithelial wound healing - Guo, Xiao-Xiao; Chang, Xue-Jiao; Pu, Qi; Li, Ao-Ling; Li, Jing; Li, Xin-Yu (Frontiers in Medicine, 2024)
To analyze the therapeutic effect and mechanism of Urolithin A (UA) on delayed corneal epithelial wound healing.The C57BL/6 mice were continuously exposed to hyperosmotic stress (HS) for seven days followed by the removal of central corneal epithelium to establish a delayed corneal epithelial wound healing model in vivo. In vitro, the human corneal epithelial cell line (HCE-T) was also incubated under HS. UA was administered in vivo and in vitro to study its effects on corneal epithelial cells. Senescence-associated β-galactosidase (SA-β-gal) staining was performed to detect the level of cell senescence. Transcriptome sequencing (RNA-seq) was conducted to elucidate the molecular mechanism underlying the effect of UA on corneal epithelial repair. Additionally, the expression of senescence-related and ferroptosis-related genes and the levels of lipid peroxides (LPO) and malondialdehyde (MDA) were measured.Results: Hyperosmotic stress (HS) significantly increased the proportion of SA-β-Gal staining positive cells in corneal epithelial cells and upregulated the expression of p16 and p21 (P < 0.0001). Topical application of UA decreased the accumulation of senescent cells in corneal epithelial wounds and promoted epithelial wound healing. The results of RNA-seq of HS-induced corneal epithelial cells showed that the ferroptosis pathway was significantly dysregulated. Further investigation revealed that UA decreased the level of oxidative stress in HCE-T cells, including the levels of LPO and MDA (P < 0.05). Inhibition of ferroptosis significantly prevented cellular senescence in HS-induced HCE-T cells.In this study, UA promoted HS-induced delayed epithelial wound healing by reducing the senescence of corneal epithelial cells through the inhibition of ferroptosis.